EFFECTS OF PRE-QUESTIONING ON THE READING COMPREHENSION ACHIEVEMENT OF THE SECOND-GRADE AT MADRASAH ALIYAH IN KAPUAS KUALA - Aziz, Abdul; Elthia, Memey Wardani; Widyawati, Widyawati; Shalehah, Mar’atus; Bahtiar, Bahtiar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the effect of pre-questions on the reading comprehension achievement of second-grade students at Madrasah Aliyah Miftahul Ulum and to examine the impact of gender on this matter. The research was conducted in the 2023/2024 academic year, involving 68 second-grade Social Science students. The method used is a factorial experiment, with data collection, coding, scoring, and analysis using the SPSS application. The sample was divided into two classes, namely, the experimental class and the control class. As for the instruments in this study, they used tests, namely: essay tests and multiple-choice tests. The essay test was used for the pre-question test and the multiple-choice test for the student's reading comprehension test. The results of this research indicate that the pre-question has a significant effect on the students' reading achievement, while gender does not have a significant effect on reading ability. Then, a better understanding was shown in the experimental class that used pre-questions compared to the control class. This can be seen from the average score results and two-way ANOVA.